A Newly Isolated Strain of Haematococcus pluvialis GXU-A23 Improves the Growth Performance, Antioxidant and Anti-Inflammatory Status, Metabolic Capacity and Mid-intestine Morphology of Juvenile Litopenaeus vannamei - Fang, HaoHang; Zhuang, ZhenXiao; Huang, LuoDong; Niu, Jin; Zhao, Wei (Frontiers in Physiology, 2022)
Haematococcus pluvialis can be used as a green additive in aquafeeds due to it contains rich astaxanthin and polyunsaturated fatty acid. In the present study, a newly strain of H. pluvialis GXU-A23 with high concentration of astaxanthin was firstly isolated by a newly culture strategy in our laboratory. In addition, H. pluvialis GXU-A23 was applied in the Litopenaeus vannamei feed for determining whether it has positive effects on the growth performance, antioxidant and anti-inflammatory status, metabolic capacity and mid-intestine morphology of juvenile L. vannamei. Shrimp with 0.63 g approximately initial body weight were fed diets supplemented with/without 50 g/kg H. pluvialis GXU-A23. After eight-weeks feeding intervention, significantly higher growth performance of L. vannamei was obtained in the H. pluvialis GXU-A23 treatment group compared to the control group (p < 0.05). At the same time, L. vannamei fed with H. pluvialis GXU-A23 acquired significantly better antioxidant and anti-inflammatory status than the control group (p < 0.05). In addition, higher RNA expression level of hepatopancreas digestive enzyme, hepatopancreas lipid and glucose metabolic enzymes as well as better mid-intestine morphology were found in the H. pluvialis GXU-A23 treatment group than the control group (p < 0.05). These results indicated that 50 g/kg H. pluvialis GXU-A23 was suitable for the L. vannamei feed, which could improve the growth performance, antioxidant and anti-inflammatory status, metabolic capacity and mid-intestine morphology of juvenile L. vannamei.